PERBANDINGAN ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PENJELAS PADA PERUSAHAAN INDUSTRI KEUANGAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Syaifudin, Mochamad Naufal (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research is to compare the bankruptcy prediction models introduced by Z-scores Altman; the First Altman model, the Revised Altman model, and the Modified Altman model to predict bankruptcy for banking companies listed in the Indonesian Stock Exchange. The research was conducted for eleven banking companies that matched criteria in the selection of the sample over the years 2010-2012 based on published data for the same period. In the descriptive method, researchers describe the model and analyze financial distress in banking companies using the size of the company where the company will be divided into small group and large group in terms of total assets. The result from this research is the First Altman model, The Revised Altman model, and banking company with assets of a small group provides the highest percentage in predicting the bankruptcy, whereas the predictive models provide healthy is The Modified Altman. Keyword : financial distress, bankruptcy index, z-score Altman model. size of the company.